2021
DOI: 10.3390/medicina57060528
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Heart Rate Tracings in Preterm Fetus

Abstract: Background and Objectives: Prematurity is currently a serious public health issue worldwide, because of its high associated morbidity and mortality. Optimizing the management of these pregnancies is of high priority to improve perinatal outcomes. One tool frequently used to determine the degree of fetal wellbeing is cardiotocography (CTG). A review of the available literature on fetal heart rate (FHR) monitoring in preterm fetuses shows that studies are scarce, and the evidence thus far is unclear. The lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Thus, we hypothesize that fetuses during moderate premature labor might exhibit a different response to stress during active labor than term fetuses. The findings presented here are in line with those of Hurtado-Sánchez et al, who reported that preterm fetuses manifested slightly higher FHR and lower amplitude decelerations compared to term fetuses evaluated by cardiotocography [40].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we hypothesize that fetuses during moderate premature labor might exhibit a different response to stress during active labor than term fetuses. The findings presented here are in line with those of Hurtado-Sánchez et al, who reported that preterm fetuses manifested slightly higher FHR and lower amplitude decelerations compared to term fetuses evaluated by cardiotocography [40].…”
Section: Discussionsupporting
confidence: 93%
“…Adequate CTG evaluation of a preterm fetus is a problematic issue in perinatology, as the lack of guidelines and evidence-based recommendations make it complicated. 19 Baseline fetal heart rate in preterm fetuses is often tachycardiac (>160 bpm) 7 and decelerations-especially in the early preterm (24-28 weeks) population-can be found more often and could be normal compared to term fetuses. 20 In our study, baseline variability pattern and absence of accelerations were studied to determine the reassuring or non-reassuring nature of cardiotocograms in the light of neonatal parameters after birth, with the concurrent study of the corresponding placental histopathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate CTG evaluation of a preterm fetus is a problematic issue in perinatology, as the lack of guidelines and evidence-based recommendations make it complicated. 19 Baseline fetal heart rate in preterm fetuses is often tachycardiac (>160 bpm) 7 and decelerations—especially in the early preterm (24-28 weeks) population—can be found more often and could be normal compared to term fetuses. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A baseline fetal heart rate status: normal between 110 to 160 bpm, Tachycardia >160 bpm, bradycardia <110 bpm [28].…”
Section: Operational Definitionsmentioning
confidence: 99%